Effect of Acid-Base Activation on Extracted Tea (Camellia sinensis) Leaf Biosorbent for Hexavalent Chromium Removal - Devianto, Luhur; Eunice, Samella; Haji, Alexander; Wirosoedarmo, Ruslan; Kurniati, Evi; Anugroho, Fajri (Graduate School, Universitas Brawijaya, 2025)
Industrial wastewater often contains heavy metals such as hexavalent chromium [Cr(VI)], a toxic and carcinogenic pollutant widely generated from activities including electroplating, leather tanning, and pigment manufacturing. Due to its high solubility and mobility in aquatic environments, Cr(VI) poses significant environmental and public health hazards, even at low concentrations. There is increasing interest in sustainable, low-cost alternatives for heavy metal removal, such as biosorption using agricultural waste materials. Tea leaves (Camellia sinensis L.), one of the most consumed beverages globally, generate a large volume of organic waste that is rich in functional groups capable of metal binding. This study investigates the potential of extracted tea leaf biomass as a biosorbent for Cr(VI) removal from aqueous solutions. The research aims to characterize the effect of acid-base activation on biosorbent by determining the optimal activation method, evaluating adsorption performance under different operational parameters, and identifying the most appropriate adsorption isotherm model. The biosorbent was prepared from ethanol-extracted green tea leaf waste (for tannin extraction that will be used for other applications) and activated using sodium hydroxide (NaOH) or sulfuric acid (H₂SO₄) at various concentrations. Fourier Transform Infra Red analysis revealed key functional groups as hydroxyl (-OH) bond responsible for metal ion binding. Activation using 0.1 M NaOH resulted in the adsorption capacity range 1.22 – 12.43 mg.g-1. The maximum Cr(VI) removal efficiency of 99.42% was achieved at a contact time of 180 minutes and an initial metal concentration of 100 ppm. Adsorption equilibrium data closely followed the Langmuir isotherm model (R² = 0.999), indicating monolayer adsorption on a homogeneous surface. These findings demonstrate that NaOH-activated of extracted tea leaf biomass still has a potential biosorbent for Cr(VI) removal, offering an option of an eco-friendly solution for wastewater treatment applications.